Inclusion of youth/young adults at public libraries : A study of how public libraries in Skåne are working to include youth/young adults through projects - Classon,Jessica (2020)
The aim of this master thesis is to investigate how public libraries through projects work to include the target group youth/young adults. To get an understanding of this I will examine five projects towards youth/young adults at public libraries in Skåne. The theoretical framework I have used is the four-space model. The method being used is an ethnographic content analysis of documents from the projects. Among the conclusions that were made are that all five projects in my study are working as a meeting place for youth/young adults. Several of the projects are aiming to create meetings between youth/young adults with different background. Three of the projects are designed to inspire the target group to read. Another conclusion is that all projects in my study are aiming for getting youth and young adults to be engaged and participating in different ways. By participating in the projects activities the youth/young adults will feel a state of belonging and becomes part of a larger context. It is possible that the participation also contributes to an increased social network. These aspects are together contributing to include youth/young adults in the public library.